Well-Characterized Polyethyleneimine-/Carboxylated-Polyethylene-Glycol-Functionalized Gold Nanoparticles as Prospective Nanoscale Control Materials for In Vitro Cell Viability Assays: Particle Characterization and Toxicity Tests in Eight Mammalian Cell Lines - Vytas Reipa; Vincent A. Hackley; Alessandro Tona; Min Beom Heo; Ye Ryeong Lee; Tae Geol Lee; Aaron Johnston-Peck; Tae Joon Cho (Nanomaterials)
The safety screening of manufactured nanomaterials (MNMs) is essential for their adoption by consumers and the marketplace. Lately, animal-based testing has been replaced by mechanistically informative in vitro assays due to the requirements of regulatory agencies. Cell viability assays are widely employed for manufactured nanomaterial hazard screening as a first-tier approach. Critical parts of such assays are positive and negative controls that serve as measurement benchmarks. We present the cellular viability and corresponding particle characterization obtained with eight different cell lines that were exposed to Au-PEI and Au-PEG-COOH nanoparticles. We showed that polyethyleneimine- and carboxylate-polyethylene-glycol-conjugated gold nanoparticles (AuPEI and Au-PEG-COOH) qualified for positive and negative controls in the in vitro cell viability assays used for MNM toxicological screening.